Post-Traumatic Counselling Through Group Games - Anne Hafina (Universitas Pendidikan Indonesia (UPI), 2023)
Post-traumatic anxiety disorder is a psychological disorder and emotional scars in individuals who have experienced tragic and extraordinary events. One form of treatment that can be done is through group counselling with the method of playing. The play method has a non-systematic process but requires cognitive, affective, and interpersonal abilities so that it is seen as capable of increasing adaptive abilities which are important for the adjustment of children in trauma conditions. The results of this study describe the achievement of the success of group games in helping traumatized children between 60% and 70% in each target area as indicated by the changes experienced by students towards a better direction in learning activities in class, social relations, and emotional conditions and feelings.